1988
DOI: 10.1093/jac/21.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcal superinfection in patients treated with ciprofloxacin

Abstract: Two patients developed serious enterococcal superinfection following therapy with intravenous ciprofloxacin. The strains causing bacteraemia were susceptible to low concentrations of ciprofloxacin when tested at a standard inoculum. However, at an inoculum of 1 X 10(7) cfu/ml they were resistant to high concentrations of ciprofloxacin. Our data suggest that ciprofloxacin should not be used to treat patients with serious enterococcal infection and that patients treated with ciprofloxacin should be monitored car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 0 publications
0
22
0
3
Order By: Relevance
“…After about 3 weeks of these various therapies, E. faecalis was found in abdominal abscesses along with P. aeruginosa, Candida spp., and Proteus vulgaris. After 5 more days of ciprofloxacin and tobramycin, the patient became bacteremic with E. faecalis (231). These patients likely represent persistence of E. faecalis following fecal spillage and illustrate the important role enterococci can play in this type of patient, even when anti-enterococcal therapy has been used.…”
Section: Endocarditismentioning
confidence: 94%
See 2 more Smart Citations
“…After about 3 weeks of these various therapies, E. faecalis was found in abdominal abscesses along with P. aeruginosa, Candida spp., and Proteus vulgaris. After 5 more days of ciprofloxacin and tobramycin, the patient became bacteremic with E. faecalis (231). These patients likely represent persistence of E. faecalis following fecal spillage and illustrate the important role enterococci can play in this type of patient, even when anti-enterococcal therapy has been used.…”
Section: Endocarditismentioning
confidence: 94%
“…In one study of 144 bacteremias in obstetrical and gynecological patients, 18 (13%) were due to enterococci, placing it second in frequency behind Escherichia coli; although the sources were not identified, it is clear that the majority were not from a urinary source (122). Enterococcal abscesses and bacteremia also occur with intraabdominal and biliary infections (53,80,129,193,231 (137). This infection occurred in 38 (6.6%) of 572 patients who had a UTI; of note, 28 of these 38 had urinary catheters, which is also considered a compounding factor in the development of enterococcal UTIs.…”
Section: Endocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such evidence several reviews on bacteremia have revealed that the source of enterococcal bacteremia is intra-abdominal infection in a significant number of cases (1,3,80). There are also several clinical reports of enterococci occurring as sole isolates in intra-abdominal infections (79,96,97). The presence of foreign bodies, such as dialysis catheters, and the use of prior antibiotics appear to be predisposing factors for enterococcal intra-abdominal infections (96,98).…”
Section: Epidemiologic Aspects Of Enterococcal Infectionmentioning
confidence: 99%
“…There are also several clinical reports of enterococci occurring as sole isolates in intra-abdominal infections (79,96,97). The presence of foreign bodies, such as dialysis catheters, and the use of prior antibiotics appear to be predisposing factors for enterococcal intra-abdominal infections (96,98).…”
Section: Epidemiologic Aspects Of Enterococcal Infectionmentioning
confidence: 99%